Cervicovaginal Complement Activation and Microbiota During Pregnancy and in Parturition - Livson, Sivan; Virtanen, Seppo; Lokki, A. Inkeri; Holster, Tiina; Rahkonen, Leena; Kalliala, Ilkka; Nieminen, Pekka; Salonen, Anne; Meri, Seppo (Frontiers in Immunology, 2022)
Background: Vaginal microbiome and the local innate immune defense, including the complement system, contribute to anti- and proinflammatory homeostasis during pregnancy and parturition. The relationship between commensal vaginal bacteria and complement activation during pregnancy and delivery is not known. Objective: To study the association of the cervicovaginal microbiota composition to activation and regulation of the complement system during pregnancy and labor. Study design: We recruited women during late pregnancy (weeks 41+5 – 42+0, n=48) and women in active labor (weeks 38+4 – 42+2, n=25). Mucosal swabs were taken from the external cervix and lateral fornix of the vagina. From the same sampling site, microbiota was analyzed with 16S RNA gene amplicon sequencing. A Western blot technique was used to detect complement C3, C4 and factor B activation and presence of complement inhibitors. For semiquantitative analysis, the bands of the electrophoresed proteins in gels were digitized on a flatbed photo scanner and staining intensities were analysed using ImageJ/Fiji win-64 software. Patient data was collected from medical records and questionnaires. Results:The vaginal microbiota was Lactobacillus-dominant in most of the samples (n=60), L. iners and L. crispatus being the dominant species. L. gasseri and L. jensenii were found to be more abundant during pregnancy than active labor. L. jensenii abundance correlated with C4 activation during pregnancy but not in labor. G. vaginalis was associated with C4 activation both during pregnancy and labor. The amount of L. gasseri correlated with factor B activation during pregnancy but not during labor. Atopobium vaginae was more abundant during pregnancy than labor and correlated with C4 activation during labor and with factor B activation during pregnancy. Activation of the alternative pathway factor B was significantly stronger during pregnancy compared to labor. During labor complement activation may be inhibited by the abundant presence of Factor H and FHL1. Conclusions: These results indicate that bacterial composition of the vaginal microbiota might have a role in the local activation and regulation of complement-mediated inflammation during pregnancy. At the time of parturition complement activation appears to be more strictly regulated than during pregnancy.